Case Report: Amphiphysin Antibody-Associated Stiff-Limb Syndrome and Myelopathy: An Unusual Presentation of Breast Cancer in an Elderly Woman - Gogia, Bhanu; Shanina, Elena; Fang, Xiang; He, Jing; Li, Xiangping (Frontiers in Neurology, 2021)
Background: Paraneoplastic stiff-limb syndrome (SLS) is a rare manifestation of underlying malignancy and could have distinctive features different from the classic stiff-person syndrome (SPS). Case Description: We present a case of anti-amphiphysin antibody (Ab)-associated paraneoplastic SLS, in an 83-year-old woman with invasive ductal carcinoma of the breast. She presented with stiffness, painful spasms of the distal legs, and asymmetrical fixed posturing of the foot. There are coexisting long-tract disturbance and lower-extremity weakness. Treatment with diazepam provided symptomatic relief while plasma exchange (PLEX) did not lead to significant clinical improvement. The patient was bedridden within 3 months and passed away within 6 months from symptom onset. Conclusion: This case highlights the importance of recognition of uncommon presentation of SPS and its oncological significance. This entity requires a high degree of suspicion for initiation of the proper workup. The rapid identification and treatment of the underlying tumor might offer the best chance for recovery.